If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + -2t) = -8 (3 * 4 + -2t * 4) = -8 (12 + -8t) = -8 Solving 12 + -8t = -8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -8t = -8 + -12 Combine like terms: 12 + -12 = 0 0 + -8t = -8 + -12 -8t = -8 + -12 Combine like terms: -8 + -12 = -20 -8t = -20 Divide each side by '-8'. t = 2.5 Simplifying t = 2.5
| 2x+(-5x+6)=6 | | A-21.23=-3.5 | | 3(2x-5)-19=12 | | r+4+7r= | | 2x-5x+6=6 | | M-0.19=12 | | 5(6y-2)-9+3(5y+3)=-25 | | -1.2(y-1)=0.8 | | 12+5=17 | | W-2.8=4.2 | | 2y-(y-0.4)=-0.8 | | x^4+12x^3+34x^2-12x+1=0 | | -1.5(x+2)=-2-(-8) | | -10-(-4n+4)=-2(9n+7) | | y=-4+11 | | x+10+1+9x= | | x+11=-5x-13 | | 227=19v-20 | | x-4.5=3.75 | | 2(-5x-9)=-60 | | -3.5+v=-2 | | -3x^2+28x+49=0 | | 4(x+3)=3x-8 | | -7x-5(-3x-20)=52 | | 12x+20+10x=180 | | 4t+-7t=9 | | -6x-8=3x-31 | | 20x-16=18x-9 | | 9x-6x+4=x-8 | | X^2-15=66 | | f(5)=4x^2-5x+2 | | 8(-7p-9)= |